Chronic kidney disease in primary care: outcomes after five years in a prospective cohort study - Shardlow, Adam; McIntyre, Natasha J.; Fluck, Richard J.; McIntyre, Christopher W.; Taal, Maarten W. (Public Library of Science, 2016)
Background